Health monitoring on the Android smartphones - Tan, Jia Qiang (2014)
This project aims help improve the health care systems for elderly such that the system can be placed at home, so that there is a safety mechanism to monitor the elderly when there is no one to look after them. It is mobile for them to carry it around on the go, or it can also be installed in their own home. The system monitors their health conditions via as their heart rate and brainwave, to check the elderly’s condition frequently. Otherwise it is able to dispense a capsule from the pill dispenser machine such that they are able to take some immediate medication first.